Research and Education of Lighting Technology at the Slovak University of Technology - Gašparovský, Dionýz (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Goal of the paper is to present approaches and solutions for organization of the educational process in light and lighting at the Slovak University of Technology as a case study with generalized outcomes that can be applied in other universities or countries. The paper aims to inspire and to draw attention on education in lighting and the necessity to exchange knowledge and experience of professionals responsible for eduction, what is nowadays felt as an underestimated topic.
Výzkum a výuka světelné techniky na Slovenské technické univerzitě
Keywords: lighting technology; light & lighting; lighting education; lighting engineering